2013
DOI: 10.1371/journal.pone.0063772
|View full text |Cite
|
Sign up to set email alerts
|

Human Fear Acquisition Deficits in Relation to Genetic Variants of the Corticotropin Releasing Hormone Receptor 1 and the Serotonin Transporter

Abstract: The ability to identify predictors of aversive events allows organisms to appropriately respond to these events, and failure to acquire these fear contingencies can lead to maladaptive contextual anxiety. Recently, preclinical studies demonstrated that the corticotropin-releasing factor and serotonin systems are interactively involved in adaptive fear acquisition. Here, 150 healthy medication-free human subjects completed a cue and context fear conditioning procedure in a virtual reality environment. Fear pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 61 publications
9
58
0
Order By: Relevance
“…The data analyzed in this study come from a sample reported on previously (Heitland et al, , 2013. The sample included 150 subjects recruited via advertisements at Utrecht University comprising 90 females and 60 males (mean age = 21.6, SD = 2.4) free of any current or previous psychiatric or neurological disorder, drug or alcohol dependence, current psychoactive medication, hearing problems and color blindness.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data analyzed in this study come from a sample reported on previously (Heitland et al, , 2013. The sample included 150 subjects recruited via advertisements at Utrecht University comprising 90 females and 60 males (mean age = 21.6, SD = 2.4) free of any current or previous psychiatric or neurological disorder, drug or alcohol dependence, current psychoactive medication, hearing problems and color blindness.…”
Section: Participantsmentioning
confidence: 99%
“…The study comprised a fear-potentiated startle (FPS) conditioning paradigm in a virtual reality environment (see Heitland et al, 2012Heitland et al, , 2013. In this paradigm, fear conditioned responding to both a threat cue and a threat context is acquired.…”
Section: Experimental Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of PD, linkage and case/control studies as well as dimensional association studies provided a heterogeneous picture [26][27][28][29] regarding an involvement of CRHR1. Notably, the initial association of this gene with PD 29 was followed up recently, providing evidence that the CRHR1 minor rs878886 allele leads to fearacquisition deficits using a fear condition protocol in healthy volunteers 30 . Furthermore, a neuroimaging study revealed that the processing of emotional stimuli crucially depends on CRHR1 genotype 31 .…”
Section: Introductionmentioning
confidence: 99%
“…50 Fear acquisition deficit is relevant in the pathogenesis of human AD. 51 Finally, we evaluated the rs746530 polymorphism of the SERPINA6 gene in AD.…”
mentioning
confidence: 99%